Effect of certain bentonite products on the temporal variation of elemental content in white wine - Rakonczás, N.; Kállai, Z.; Antal, G.; Kovács, B.; Holb, I. J. (International Journal of Horticultural Science, 2026)
The ’terroir’ character of wines can be shaped with certain technological elements such as bentonite fining. Bentonite is an agent used for the removal of thermolabile proteins in wines. However, during fining, the quantity of certain wine components can change, including the elemental composition of the wine. According to the recommendations of bentonite suppliers, wines should be racked off the bentonite fining sediment within 2-3 weeks. However, in winemaking practice, wines can remain on bentonite fining sediment for up to 1-4 months. One reason for this is that racking wines off the sediment has a negative impact on wine quality. Thus, it is a question of how much the later or earlier racking time can alter the elemental content of the wine. Our study aimed to examine the elemental content of wines treated with three different bentonite products sampled from over the bentonite fining sediment at various time points. Our investigation was conducted with the 2019 vintage white wine of the University of Debrecen. Fining was performed with three bentonite products: Nucleobent, BW200, and Granubent Poretec. The sampling schedule following fining was: 0 days - unfined control, 7th, 14th, 27th, 56th, and 85th days. The macro-, meso-, and microelement contents (P, K, Ca, Mg, S, Al, Na, B, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Cd, Ba, and Pb) of the wines were determined using ICP OES and ICP MS devices. Our results showed significant changes in the Al, Na, Cr, Fe, Co, Ni, Sr, Ba, Cu, and Pb contents of the wines depending on the sampling time. It is noteworthy that all three bentonite products increased the Al and Pb contents of the wines. For Fe, dynamic increases were observed over time with the BW200 product, reaching the threshold value of susceptibility to brakeage. However, from a winemaking technology perspective, it was favorable for the Cu content of the wines to decrease with both earlier and later racking times, for all bentonite products examined. Based on the elemental analyzes of the white wines studied, it can be concluded that racking of wines should be timed according to the recommendations of suppliers.